PENGAWASAN DINAS TATA RUANG DAN BANGUNAN TERHADAP ALIH FUNGSI BANGUNAN RUMAH TOKO (RUKO) DI KOTA PEKANBARU TAHUN 2013 - Rizky Pratama T; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The economic development of the city of Pekanbaru Increasingly rapid impact on the progress of development. The development progress itself in the form of the construction of home store buildings (ruko) that occur in all the sub-district in the city of Pekanbaru. Home store buildings (ruko) is a building used as a place to live and a place to do business. Their home store buildings (ruko) were switching function having a negative impact, so that the switch functions of supervision of the home store buildings (ruko) to address the deviations is a serious matter. The method used in this research is qualitative. So that the collected data is the data is derived from interviews, documentation, and observation. By using qualitative methods will provide more fundamental problems and deep switch functions related to the supervision of the home store buildings (ruko). The results of this research, monitoring implementation of the conversion of home store buildings (ruko) in the city of Pekanbaru has not fully maximized. Judging from the shape of the oversight conducted, coordination between instant Occurs competent and conditions of inspectors charged with overseeing the conversion of home store buildings (ruko). Coupled with the limitations of strategic land and less accommodating regulation be a driving force going over the home store buildings (ruko). This is evidenced by many home store buildings (ruko) who converted to hotels, karaoke bars, schools, boarding houses and others. The transformation of the home store buildings (ruko) is negatively impacted, Become have many places to do any unlawful activity, irregular urban planning and traffic that can not be predicted. With the Regional Regulation No. 14 of 2000 on Building Permits Considered was not a accommodate the times. Keywords: Monitoring, Switch Function, Regional Regulation